How do you solve the system of equations -4x + 6y = 4 and - x + 8y = 1?

1 Answer
Nov 28, 2016

{(x = -1), (y = 0) :}

Explanation:

{(-4x + 6y = 4), (-x + 8y = 1) :}

{(-4x + 6y = 4), ( (-x + 8y = 1) * (-4)) :}

{(-4x + 6y = 4), (4x - 32y = -4) :}

Add these together to get

-26y = 0

Therefore

y=0

Plug 0 in for y in one of the equations like so:

-x + (8 * 0) = 1

-x = 1

x = -1

Check your answer by putting 0 in for y and -1 in for x in the other equation like so:

(-4 x -1) + (6 * 0) = 4

4 + 0 = 4

4 = 4

:)